The Effect Of Role Play Method On English Speaking Ability Of Vocational High School Students - Adkia, Vania Klaresta; Mufaridah, Fitrotul; Oktarini, Widya (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the effect of the role play method on the English speaking ability of vocational high school students. Many students face difficulties in speaking English due to limited vocabulary, incorrect pronunciation, low self-confidence, and other factors. This research used a quasi-experimental method conducted at SMK Muhammadiyah Jember, which was divided into two groups: the experimental group, which received treatment using the role play method, and the control group, which was taught using the conventional method. The data collection method used was a test, consisting of a pre-test and post-test, and the results were analyzed using SPSS version 27. Based on the research findings, the analysis showed a significant effect on the speaking ability of students in the experimental group, with an average score of 58.23, compared to the control group, which had an average score of 39.67, with a significance level of 0.05. These results show that the role play method had a significant effect on students' speaking ability and it can be concluded that the role play method is effective to be used as a variation in teaching English.